PASTA kinase-dependent control of peptidoglycan synthesis via ReoM is required for cell wall stress responses, cytosolic survival, and virulence in Listeria monocytogenes. - Jessica L Kelliher (Public Library of Science (PLoS), 2021)
Pathogenic bacteria rely on protein phosphorylation to adapt quickly to stress, including that imposed by the host during infection. Penicillin-binding protein and serine/threonine-associated (PASTA) kinases are signal transduction systems that sense cell wall integrity and modulate multiple facets of bacterial physiology in response to cell envelope stress. The PASTA kinase in the cytosolic pathogen Listeria monocytogenes, PrkA, is required for cell wall stress responses, cytosolic survival, and virulence, yet its substrates and downstream signaling pathways remain incompletely defined. We combined orthogonal phosphoproteomic and genetic analyses in the presence of a β-lactam antibiotic to define PrkA phosphotargets and pathways modulated by PrkA. These analyses synergistically highlighted ReoM, which was recently identified as a PrkA target that influences peptidoglycan (PG) synthesis, as an important phosphosubstrate during cell wall stress. We find that deletion of reoM restores cell wall stress sensitivities and cytosolic survival defects of a ΔprkA mutant to nearly wild-type levels. While a ΔprkA mutant is defective for PG synthesis during cell wall stress, a double ΔreoM ΔprkA mutant synthesizes PG at rates similar to wild type. In a mouse model of systemic listeriosis, deletion of reoM in a ΔprkA background almost fully restored virulence to wild-type levels. However, loss of reoM alone also resulted in attenuated virulence, suggesting ReoM is critical at some points during pathogenesis. Finally, we demonstrate that the PASTA kinase/ReoM cell wall stress response pathway is conserved in a related pathogen, methicillin-resistant Staphylococcus aureus. Taken together, our phosphoproteomic analysis provides a comprehensive overview of the PASTA kinase targets of an important model pathogen and suggests that a critical role of PrkA in vivo is modulating PG synthesis through regulation of ReoM to facilitate cytosolic survival and virulence.